PELAKSANAAN PEMBELAJARAN BCCT BAGI ANAK USIA DINI; STUDY PELAKSANAAN BCCT DI TK ISLAM MUJAHIDIN PONTIANAK - Nur Hamzah (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2016)
Nowadays, there are a lot of pre-school educational institution such as Kindergarten (TK), Raudhatul Atfhal (RA), Playgrounds, Children Care, Early Childhood Education (PAUD), and so forth. Furthermore, in these educational institution, study method and approach is developed based on earl childhood characters. One of the ways is named Beyond Centres and Circle Times (BCCT). Moreover, the BCCT is theoretically a study approach which is held at the centre or cirlce. The children apparently learn something based on their themes and centre. Besides, there are still few pre-school institutions performed this model on their schools because it provides more human resources, spaces, and budget. In Pontianak, some schools have applied this method, and one of them is TK Islam Mujahidin.